Embedding complete multi-partite graphs into Cartesian product of paths and cycles - R. Sundara Rajan; A. Arul Shantrinal; T.M. Rajalaxmi; Jianxi Fan; Weibei Fan (Electronic Journal of Graph Theory and Applications (EJGTA), 2021)
Graph embedding is a powerful method in parallel computing that maps a guest network G into a host network H. The performance of an embedding can be evaluated by certain parameters, such as the dilation, the edge congestion, and the wirelength. In this manuscript, we obtain the wirelength (exact and minimum) of embedding complete multi-partite graphs into Cartesian product of paths and/or cycles, which include n-cube, n-dimensional mesh (grid), n-dimensional cylinder, and n-dimensional torus, etc., as the subfamilies.